2017
DOI: 10.1177/0003702817691289
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy Enhancement of Raman Spectroscopy Using Complementary Laser-Induced Breakdown Spectroscopy (LIBS) with Geologically Mixed Samples

Abstract: Quantitative Raman analysis was carried out with geologically mixed samples that have various matrices. In order to compensate the matrix effect in Raman shift, laser-induced breakdown spectroscopy (LIBS) analysis was performed. Raman spectroscopy revealed the geological materials contained in the mixed samples. However, the analysis of a mixture containing different matrices was inaccurate due to the weak signal of the Raman shift, interference, and the strong matrix effect. On the other hand, the LIBS quanti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…On the other hand, LIBS has high accuracy in the quantitative analysis of atomic carbon and calcium in mixed samples. For the mixture of calcite and gypsum, the coefficient of atomic carbon measured by LIBS is 0.99, while the signal measured by Raman spectroscopy is less than 0.9. erefore, they first used Raman spectroscopy to obtain the geological components of the mixed samples and then conducted LIBS-based quantitative analysis of the Raman spectroscopy results to construct a high-precision univariate calibration curve [5]. Raman spectra reflect the vibration and rotation of molecules in matter.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, LIBS has high accuracy in the quantitative analysis of atomic carbon and calcium in mixed samples. For the mixture of calcite and gypsum, the coefficient of atomic carbon measured by LIBS is 0.99, while the signal measured by Raman spectroscopy is less than 0.9. erefore, they first used Raman spectroscopy to obtain the geological components of the mixed samples and then conducted LIBS-based quantitative analysis of the Raman spectroscopy results to construct a high-precision univariate calibration curve [5]. Raman spectra reflect the vibration and rotation of molecules in matter.…”
Section: Introductionmentioning
confidence: 99%
“…We therefore propose to combine different analytical methods (in this case, µ-EDXRF, LIBS and Raman spectroscopy) for the analysis of mineralogical samples to obtain both elemental and molecular information, as well as information on the crystal structure, which makes it possible to identify even isochemical phases. It has already been shown that the combination of analytical methods that deliver both elemental as well as molecular information can be beneficial for the classification of mineral samples [4,[25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…Recently also some works focused on how to merge LIBS spectra and Raman spectra in classification. [ 30–37 ] Even though these merging methods of two kinds of spectra have been used in analyzing renal calculi, [ 30 ] geologically mixed samples, [ 31 ] plastics, [ 32 ] Mars mineralogy, [ 33,34 ] fluorine, [ 35 ] and bacteria, [ 36,37 ] parts of these works focus on using elemental or molecular information reflected by LIBS and Raman spectra separately, not the comprehensive processing of these information. Even though some methods preformed comprehensive data processing using chemometrics and machine learning methods, these works only merged the spectral information in data fusion level.…”
Section: Introductionmentioning
confidence: 99%